Elimination kinetics of ceftiofur hydrochloride in milk after an 8-day extended intramammary administration in healthy and infected cows. - Rongwei Han; Songli Li; Jun Wang; Zhongna Yu; Jiaqi Wang; Nan Zheng (PLoS ONE, 2017)
Ceftiofur hydrochloride (CEF) is occasionally used for the intramammary (IMM) treatment of mastitis. This extralabel manner could result in a drug-residue violation of the milk. The objective of this study was to determine the elimination kinetics of IMM CEF in lactating dairy cattle. The pharmacokinetic profile of CEF after repeated IMM administration in nine healthy cows and nine Staphylococcus aureus infected cows was investigated, alongside determining the MICs of Staph. aureus field strains. The MIC 90 value for CEF in Staph. aureus field strains (n = 31) was 0.25 μg/mL. The t >MIC CEF values for low- production quarters were longer than those for high- and mid- production quarters. The results showed that ceftiofur was detected in milk up to 108 h after the last infusion in both healthy and infected cows. Cows with low milk production eliminate IMM drugs more slowly than cows with higher production. Our findings suggest that this extralabel use is not encouraged and a prudent use is recommended for mastitis therapy. The use of CEF should be reserved for infections where susceptibility tests indicate its efficacy and when alternatives are not available.